The high cost of accurate knowledge - Sutcliffe, Kathleen M.; Weber, Klaus (Harvard Business Review, 2003)
Many business thinkers believe it's the role of senior managers to sca n the external environment to monitor contingencies and constraints, a nd to use that precise knowledge to modify the company's strategy and design. As these thinkers see it, managers need accurate and abundant information to carry out that role. According to that logic, it makes sense to invest heavily in systems for collecting and organizing compe titive information. Another school of pundits contends that, since tod ay's complex information often isn't precise anyway, it's not worth go ing overboard with such investments. In other words, it's not the accu racy and abundance of information that should matter most to top execu tives–rather, it's how that information is interpreted. After all, the role of senior managers isn't just to make decisions; it's to set dir ection and motivate others in the face of ambiguities and conflicting demands. Top executives must interpret information and communicate tho se interpretations–they must manage meaning more than they must manage information. So which of these competing views is the right one? Rese arch conducted by academics Sutcliffe and Weber found that how accurat e senior executives are about their competitive environments is indeed less important for strategy and corresponding organizational changes than the way in which they interpret information about their environme nts. Investments in shaping those interpretations, therefore, may crea te a more durable competitive advantage than investments in obtaining and organizing more information. And what kinds of interpretations are most closely linked with high performance? Their research suggests th at high performers respond positively to opportunities, yet they aren' t overconfident in their abilities to take advantage of those opportun ities.
Keywords: Administrative Personnel; Data Collection; Decision Making; Organizational; Economic Competition; Information Management; Investments; Marketing; Organizational Innovation; United States